“M-Six Craft” Fashion Ecoprint Product Packaging Design Training - UMKM Marinda, Manyar Indah, Surabaya - Widyasari; Sri Wulandari; Aditya Rahman Yani; Handy Octoriawan; Mochammad Al-Hadad Firmansyah (Future Science, 2021)
The Surabaya City Government annually has programs in developing the City of Surabaya, one of which is the